Feeding Regime and Management of Captive Saltwater Crocodile, Crocodylus Porosus in Kota Tinggi, Johor - Mohd Faudzir , Najmuddin; Hassem, Siti Hasmaliza; Mohd Hauri, Nurhizatul Safikah; Zahari, Fatin; Othman, Nursyuhada; Haris, Hidayah; Abu Bakar, Muhammad Abdul Latiff (Journal of Sustainable Natural Resources, 2021)
Crocodylus porosus is the largest species of crocodile and can be found in estuarine and riverine area in Malaysia. Crocodile in captivity can be found in Malaysia for various purposes such as tourism, conservation and leather industry. However, the management practice in established crocodile farm varies across park for example in terms of feeding regime. Thus, this study focusses on the feeding regime of C. porosus in captivity and evaluation of management of crocodile of Teluk Sengat Crocodile Farm. This study was carried out for 35 days in two different ponds of Teluk Sengat Crocodile Farm, Kota Tinggi, Johor. The results show majority of the food given to crocodile were chicken (64%), followed by fish (28%) and prawn (8%). Prawn was only given to juvenile crocodile every day, while fish and whole chicken were given to adult crocodile once a week. The feeding frequency are adequate for the juvenile crocodile however, the feeding quantity for adult pond are worrying. Future research should be conducted on other captive population of C. porosus in other areas in Malaysia as well to better understand the overall management practices in Malaysia.